1996
DOI: 10.1007/bf02529728
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of the growth of femoral trabecular bone in ovariectomized rats by the novel parathyroid hormone fragment, hPTH-(1–31)NH2 (Ostabolin)

Abstract: The human parathyroid hormone, hPTH-(1-84), and its hPTH-(1-34) fragment are promising anabolic agents for treating osteoporosis because they can strongly stimulate the production of biomechanically effective cortical and trabecular bone in osteopenic ovariectomized (OVX) rats and trabecular bone in osteoporotic postmenopausal humans. The ideal PTH fragment for treating osteoporosis would be the smallest and functionally simplest fragment that activates only one signal mechanism and still strongly stimulates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 48 publications
3
41
0
Order By: Relevance
“…Some differences in microarchitecture (ConnD), in favor of inducing a more plate-like structure, were observed with G 1 ,R 19 (1-34) versus the other two peptides (Table 1), but these were not consistent between vertebra and femur and thus are of uncertain significance. These results suggest that the cAMP/PKA response to the PTH1R activation is the major determinant of the anabolic response of trabecular bone, a conclusion concordant with observations of others [1,11,18,22,30] [4]. μCT analysis of cortical bone at the mid-femoral shaft showed that PTH decreased medullary area and increased bone area, cortical thickness and the ratio of bone to total area without altering total cross-sectional area -changes consistent with a predominant endosteal apposition of new bone and consistent with other reports of intermittent PTH action in cortical bone of female mice [3].…”
Section: Discussionsupporting
confidence: 91%
“…Some differences in microarchitecture (ConnD), in favor of inducing a more plate-like structure, were observed with G 1 ,R 19 (1-34) versus the other two peptides (Table 1), but these were not consistent between vertebra and femur and thus are of uncertain significance. These results suggest that the cAMP/PKA response to the PTH1R activation is the major determinant of the anabolic response of trabecular bone, a conclusion concordant with observations of others [1,11,18,22,30] [4]. μCT analysis of cortical bone at the mid-femoral shaft showed that PTH decreased medullary area and increased bone area, cortical thickness and the ratio of bone to total area without altering total cross-sectional area -changes consistent with a predominant endosteal apposition of new bone and consistent with other reports of intermittent PTH action in cortical bone of female mice [3].…”
Section: Discussionsupporting
confidence: 91%
“…The ColI(2.3)ϩ/Rs1ϩ mice display several unique and unexpected characteristics, including a crucial temporal requirement for Rs1 expression, an unusually large amount of bone mineral accrual, and effects on bone macroarchitecture. Our results add to prior studies (10)(11)(12)(13)(14)(15) that support the anabolic role of G s signaling in osteoblasts by using a model system that controls G s activation without potential confounding effects from endogenous ligands or nonskeletal PTHR1 activation. In addition, Rs1 basal signaling activity appears to be selective for the G s pathway, with little or no activation of the G q pathway.…”
Section: Discussionsupporting
confidence: 70%
“…Our studies demonstrate that osteoblast expression of Rs1, an engineered G s -coupled RASSL with constitutive G s activity, induces a dramatic anabolic bone effect that is significantly different from previous models (10)(11)(12)(13)(14)(15). The ColI(2.3)ϩ/Rs1ϩ mice display several unique and unexpected characteristics, including a crucial temporal requirement for Rs1 expression, an unusually large amount of bone mineral accrual, and effects on bone macroarchitecture.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…However, continuous administration of PTH as an infusion in rats with intact ovarian function has been repeatedly shown to result in a catabolic response in the skeleton [6][7][8][9][10] . The ovariectomized (OVX) rat model has been used to investigate the effects of antiresorptive agents as well as PTH fragments on bone [11][12][13][14][15] . This model combines the easy manageability of rats with the main features of postmenopausal osteoporosis in women 5,14,15 .…”
Section: Introductionmentioning
confidence: 99%